Tackle and impact detection in elite Australian football using wearable microsensor technology - Gastin, P. B.; Mclean, O. C.; Breed, R. V. P.; Spittle, M. (Journal of Sports Sciences, 2014)
The effectiveness of a wearable microsensor device (MinimaxXTM S4, Catapult Innovations, Melbourne, VIC, Australia) to automatically detect tackles and impact events in elite Australian football (AF) was assessed during four matches. Video observation was used as the criterion measure. A total of 352 tackles were observed, with 78% correctly detected as tackles by the manufacturer`s software. Tackles against (i.e. tackled by an opponent) were more accurately detected than tackles made (90% v 66%). Of the 77 tackles that were not detected at all, the majority (74%) were categorised as low-intensity. In contrast, a total of 1510 "tackle" events were detected, with only 18% of these verified as tackles. A further 57% were from contested ball situations involving player contact. The remaining 25% were in general play where no contact was evident; these were significantly lower in peak Player Load™ than those involving player contact (P < 0.01). The tackle detection algorithm, developed primarily for rugby, was not suitable for tackle detection in AF. The underlying sensor data may have the potential to detect a range of events within contact sports such as AF, yet to do so is a complex task and requires sophisticated sport and event-specific algorithms.